DESAIN LAPORAN KEUANGAN BERBASIS MICROSOFT EXCEL PADA TOKO BERKAT - Andreuw Pantow (Politeknik Bisnis Indonesia, 2022)
This study aims to design the financial statements of Toko Berkat using the Microsoft Excel application. The research method was qualitative. Instruments of data collection was down through interview in the form of questions regarding the recording of financial statements. While the data collection instrument with documentation, was done through namely evidence of transactions that occurred in the business. The system for recording financial reports at Toko Berkat is still done manually without using an application, so the accounting recording process is not in accordance with SAK EMKM. The financial reports at Toko Berkat are designed using Microsoft Excel. This research can overcome the problem of recording financial statements at Toko Berkat, although in practice the owner is still assisted by researchers to process financial reports using the system that has been created.